THE EFFECT OF A PEER SUPPORT BASED NURSING EDUCATION PROGRAM ON ADOLESCENT ENGAGEMENT IN HEALTH SELF-MANAGEMENT - Nurharlinah, Nurharlinah; Karyatain, Karyatain; Herdiani, Rini (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
Adolescence is a critical phase in individual development, where awareness and skills in managing self-health are very important to be formed. This study aims to determine the effect of a peer support-based nursing education program on adolescent involvement in self-health management. The research method used was a quasi-experimental with a pretest-posttest design and a control group. The subjects of the study were adolescents aged 15–18 years who were selected purposively from two high schools. The intervention was given in the form of a nursing education session facilitated by peers (peer educators) for four weeks. Data were collected through a validated self-health involvement questionnaire and analyzed using paired t-test and independent t-test statistical tests. The results showed a significant increase in the level of adolescent involvement in the intervention group compared to the control group (p < 0.05). These findings indicate that the peer support approach is effective in increasing adolescent awareness and participation in managing their health. This program is recommended as a relevant and sustainable health promotion strategy in the school environment